A Comparative Analysis of ETR and CIR as Proxies for Tax Planning - Bimasa, Fitria (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This study aims to analyze the comparative explanatory power of the Effective Tax Rate (ETR) and the Capital Intensity Ratio (CIR) as proxies for corporate tax planning. Using a quantitative approach with a comparative design, this research employs panel data from the audited financial reports of 25 non-financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The findings indicate that both ETR and CIR are significant indicators of tax planning, as measured by the Cash Effective Tax Rate (CETR). A positive relationship was found between ETR and tax planning, suggesting consistency between reported and paid taxes in the Indonesian context. In contrast, a significant negative relationship was identified between CIR and tax planning, confirming that higher capital investment leads to a lower cash tax burden due to depreciation allowances. Furthermore, the analysis demonstrates that CIR has a stronger and more consistent explanatory power in predicting tax planning behavior compared to ETR. The study concludes that while both metrics are relevant, CIR serves as a more robust structural proxy, offering more reliable insights for stakeholders in assessing tax strategies, particularly in investment-incentivized environments like Indonesia.